1995
DOI: 10.1002/jso.2930590311
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the axillary breast

Abstract: A review of the world literature regarding carcinoma of ectopic breast tissue along with the addition of one case is reported. A total of 90 cases of carcinoma of ectopic breast tissue were found, 64 of which occurred in the axilla. The combined survival beyond the 4-year post-treatment period was 9.4%. No survival advantage was found for radical or modified radical mastectomy over that of local excision combined with axillary dissection or radiation. The addition of radiation therapy to either type of mastect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
136
0
6

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(142 citation statements)
references
References 9 publications
0
136
0
6
Order By: Relevance
“…However, Cogwells and Czerny reported that ipsilateral mastectomy does not result in an improved prognosis for patients with ectopic breast carcinoma (25). Evans and Guyton suggested that radical or modified radical surgery offered no advantage over local excision combined with axillary dissection or radiation with respect to outcome (2). It has been proposed that the surgical procedure of choice for ectopic breast carcinoma involves a wide resection of the tumour with surrounding tissue, including the skin and regional lymph nodes (3,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Cogwells and Czerny reported that ipsilateral mastectomy does not result in an improved prognosis for patients with ectopic breast carcinoma (25). Evans and Guyton suggested that radical or modified radical surgery offered no advantage over local excision combined with axillary dissection or radiation with respect to outcome (2). It has been proposed that the surgical procedure of choice for ectopic breast carcinoma involves a wide resection of the tumour with surrounding tissue, including the skin and regional lymph nodes (3,26).…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up data is provided for a limited number of patients, indicating a four-year post-treatment survival of 9.4%, which has been calculated in a meta-analysis (2). At the time of diagnosis, the majority of patients with accessory breast carcinoma were in an advanced clinical stage, with nodal metastases or an unresectable tumour due to size (20,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer originating from accessory or aberrant breast tissue has been reported with an incidence of 0.3-0.6% of all breast cancers, and 70-80% of these cases originated from the axillar region. But occurrence in the infraclavicular area, sternal area, upper abdominal area near the xiphoid process, and genital area has also been reported [1,4]. Here we report a malignant tumor arising from aberrant breast tissue, which was initially suspected as inflammatory or metastatic lymphadenopathy.…”
Section: Introductionmentioning
confidence: 85%
“…As the embryo develops, all but the pectoral portion of the original mammary ridge at the area of the fourth intercostal space resolves, leaving normal bilateral pectoral breast tissue [1]. Ectopic breast tissue has been found in multiple locations along the milk line from the axilla to the vulva.…”
Section: Introductionmentioning
confidence: 99%